Internalisasi Karakter Disiplin melalui Program Tahfiḍ Al-Qur’an di Madrasah Aliyah Mambaul Huda Desa Sendang Kec. Jambon Kab. Ponorogo - Taufiqurrohman Taufiqurrohman; Mariana Mariana (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
Character education is the foundation of life. Nowadays, character education still needs special attention due to the many phenomena that indicate a moral crisis ranging from children, teenagers, to adults. One of the character values ​​that needs to be developed is discipline. Starting with this disciplined character, it is hoped that other good characters will emerge. This study aims to find out the Tahfidzul Qu'ran Program, find out the internalization of disciplinary character through the Tahfiḍ Al-Qur'an program, and find out the supporters and obstacles in the internalization of disciplinary character through the Tahfiḍ Al-Qur'an program among Madrasah Aliyah Mambaul Huda Sendang students. Meanwhile, the method used by researchers is qualitative. The research results concluded: (1) The Tahfiḍ Al-Qur'an program uses the method as in the Yanbu'a book, namely reading, writing and memorizing the Al-Qur'an which is arranged based on the level of learning the Al-Qur'an (2) Internalizing the character of discipline through Tahfiḍ Al-Qur'an program, namely through encouragement from madrasas by requiring students to memorize juz 1, juz 2 and juz 3 of the Al-Quran, example from the teacher council and teachers of the Tahfiḍ Al-Qur'an program, and support and motivation for students (3) The supporting factor in the program is that all students live in the boarding school. There are religious lessons that can make it easier to understand the contents of the Koran. Meanwhile, the inhibiting factors are laziness, the level of students' ability to receive lessons, and the presence of students who are busy with extracurricular activities such as Scouts and OSIS.